Gut microbiota distinct between colorectal cancers with deficient and proficient mismatch repair: A study of 230 CRC patients - Min Jin; Min Jin; Jingjing Wu; Jingjing Wu; Linli Shi; Linli Shi; Bin Zhou; Bin Zhou; Fumei Shang; Xiaona Chang; Xiaochuan Dong; Shenghe Deng; et al. (Frontiers in Microbiology, 2022)
Colorectal cancers (CRCs) with deficient DNA mismatch repair (dMMR) and proficient DNA mismatch repair (pMMR) exhibit heterogeneous tumor characteristics, distinct responses to immunotherapy, and different survival outcomes. However, it is unclear whether gut microbiota is distinct between CRCs with different MMR status. In this study, we used immunohistochemistry for four major MMR proteins to determine the MMR status in 230 CRC patients. The gut microbiota was profiled in cancerous and adjacent normal tissues by using bacterial 16S rRNA sequencing. The differences in microbiota diversity, composition and related metabolic pathways between patients with dMMR and pMMR CRCs were explored. Linear discriminant analysis effect size (LEfSe) analysis was further applied to validate the significant taxonomic differences at the genus level. In our study cohort, dMMR status was identified in 29 of 230 (12.61%) tumors. The richness (alpha-diversity) of gut microbiome in dMMR tumor tissue was higher compared with pMMR tumor tissues. The microbial community composition (beta-diversity) between the two groups was significantly different. The dMMR group was enriched considerably for some microbiota, including Fusobacteria, Firmicutes, Verrucomicrobia, and Actinobacteria at the phylum level and Fusobacterium, Akkermansia, Bifidobacterium, Faecalibacterium, Streptococcus, and Prevotella bacteria at the genus level. However, the pMMR group was dominated by Proteobacteria at the phylum level and Serratia, Cupriavidus and Sphingobium at the genus level. Moreover, a wide variety of microbiota associated functional pathways were observed with different MMR status. KEGG pathway analysis indicated a higher abundance of the biosynthesis and metabolic pathways of glycan and nucleotide, cell growth and death pathways, genetic replication and repair pathways in dMMR samples compared with the pMMR group. These findings demonstrate that CRC patients with different MMR status have distinct gut bacterial community richness, compositions and related metabolic pathways, suggesting basis that may explain the effectiveness of immunotherapy in dMMR tumors.